The Effect of Empowerment and Knowledge Sharing on Teacher Productivity with Academic Supervision as an Intervening Variable - Sudiyah Anawati; Sri Setyaningsih; Dian Wulandari (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This research aims to analyze the role of academic supervision as a mediating variable in the relationship between empowerment and knowledge sharing on teacher productivity among Islamic Integrated Elementary School (SDIT) teachers in 5 sub-districts in East Jakarta. Theoretically, empowerment through the delegation of authority and trust, as well as knowledge sharing through the exchange of experiences and learning strategies, is expected to enhance productivity; however, their direct influence is not always significant. Academic supervision, including professional coaching and feedback, is expected to strengthen this relationship. This study employs a quantitative correlational approach with path analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 176 SDIT teachers selected using a multistage random sampling technique. The results indicate that knowledge sharing has no significant direct effect on teacher productivity (r = 0.135, p = 0.170). Empowerment (r = 0.236, p < 0.002) and knowledge sharing (r = 0.735, p < 0.000) have a significant effect on academic supervision. Meanwhile, academic supervision significantly mediates the relationships between empowerment (r = 0.735, p < 0.000) and knowledge sharing (r = 0.392, p < 0.000) and teacher productivity. This finding affirms the importance of academic supervision in improving the effectiveness of empowerment and knowledge collaboration in the school environment